PERANCANGAN SISTEM INFORMASI PENJUALAN MOTOR LISTRIK PT. TALABU - Edo Arribe; Anjally Jayema; Fikri Wanda Putra (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
This journal discusses the information system that will be designed as a means of selling electric motor by PT Talabu.Traditional motor cars are being replaced by more ecologically friendly electric motors, which are growing in popularity. PT. Talabu, an electric motor sales company, faces problems in inventory management and sales processes. This study's primary goal is to develop a sales information system that can help PT. Talabu in managing inventory and its operations. This research uses system needs analysis, database design, and user interface development. At the stage of analysis of system needs, the researchers found the primary needs of PT. Talabu to conduct sales operations and inventory management. This analysis shows that a database is intended to store data about customers, electric motors, and sales transactions. In addition, the app is simple to use and user-friendly.